WHICH LEAN PRACTICES DRIVE OPERATIONAL PERFORMANCE? A CONCEPTUAL FRAMEWORK FOR THE MALAYSIAN ELECTRICAL AND ELECTRONICS INDUSTRY - Ishak, Mohamad Shaufi; Anuar, Azyyati; Law , Kuan Kheng (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
This paper develops a conceptual framework examining how six Lean Manufacturing Practices (LMPs) influence Operational Performance (OP) in the Malaysian Electrical and Electronics (E&E) industry. OP is conceptualized through cycle time, defect rate, on-time delivery, and cost efficiency. Although lean manufacturing is widely recognized as a driver of operational excellence, empirical evidence from emerging-economy manufacturing contexts remains inconsistent, suggesting that individual lean practices may not contribute equally across industrial settings. Drawing on the Resource-Based View (RBV) and the Toyota Production System (TPS), the paper proposes that Cellular Manufacturing, Pull System, Continuous Improvement, Total Quality Management, Total Productive Maintenance, and Small Lot Production exert differential influences on OP in a mature, capital-intensive industry. The Malaysian E&E context is theoretically distinctive because it combines long-standing multinational lean adoption, stringent international quality requirements, short product life cycles, and high capital intensity. Six propositions are developed to guide future empirical research. The paper contributes to lean scholarship by conceptualizing lean implementation as a portfolio of practices rather than a uniformly beneficial bundle, and by offering a context-specific framework aligned with Malaysia’s National Industrial Master Plan 2030 and National Semiconductor Strategy.